Public-private Partnerships’ concepts and approaches - Nalvarte Salvatierra, Pierre (2017)
In this paper, the author gives a lecture about Public-Private Partnership (PPP). At first, he presents the nuances about its concept. After that, he writes about its classification, from his point of view and the normative. Later, he details the PPP’s phases, focusing on a pair of them. Finally, he talks about the different actors involved in PPP’s, according to each phase.All of this, giving examples of national cases through the entire article.